Pomen tveganega kapitala pri financiranju malega podjetništva - Robnik, Lidija (Naše gospodarstvo, 2006)
Due to the appearance of new knowledge and managerial approaches, entrepreneurship has developed substantially and the career of the entrepreneur has become more attractive. Venture capital has become an important source for financing the growth of small enterprises. Venture capital funds are a form of financing intended for prospective dynamic companies that cannot obtain financing from banks. Venture capital takes the form of proprietary capital since it enters the company as a co-owner for a specified time, and it exits at an agreed upon time and in a specified manner.The fund tries to create value added in a company since it is not merely a financial source but also a business relationship.
Keywords: zasebno podjetje; podjetništvo; financiranje; Das Kapital; kapital; tvegani kapital; investicije